Respuesta :
Answer:
The value of x in this equation is -4.
Step-by-step explanation:
2(4x - 6) = 4(3x - 7)
Distribute 2 to (4x - 6) and distribute 4 to (3x - 7)
8x - 12 = 12x - 28
Subtract 12x form both sides of the equation.
-4x - 12 = -28
Add 12 to both sides of equation.
-4x = 16
Divide -4 on both sides of the equation.
x = -4
The value of x is -4.
Answer:
x=4
Step-by-step explanation:
Starting with 2(4x-6) you apply the distributive law: a(b-c) = ab - ac
a =2, b=4x, c=6
2(4x-6) = 2*4x-2*6 Then multiply the numbers 2*4
8x-2*6 = multiply 2*6
8x-12
Then for 4(3x-7) you apply the distributive law.
a =4, b=3x, c=7
4*3x-4*7 multiply 4*3
12x-4*7 multiply 4*7
12x-28
Then the equation would be 8x-12 = 12x-28. Add 12 to both sides.
8x=12x-16 Subtract 12x to both sides
-4x=-16 divide both sides by -4
then you'll get Positive 4 as your x.